The regulation of interleukin 7 receptor alpha internalization, recycling and degradation by IL-7:-possible implications in T-cell homeostasis, migration and - Henriques, Catarina Martins de Oliveira, 1983- (2012)
Tese de doutoramento, Ciências Biomédica (Ciências Biopatológicas), Universidade de Lisboa, Faculdade de Medicina, 2010